2010
DOI: 10.1111/j.1365-2664.2010.01925.x
|View full text |Cite
|
Sign up to set email alerts
|

Additional carbon sequestration benefits of grassland diversity restoration

Abstract: Summary1. In Europe, grassland agriculture is one of the dominant land uses. A major aim of European agri-environment policy is the management of grassland for botanical diversity conservation and restoration, together with the delivery of ecosystem services including soil carbon (C) sequestration. 2. To test whether management for biodiversity restoration has additional benefits for soil C sequestration, we investigated C and nitrogen (N) accumulation rates in soil and C and N pools in vegetation in a long-te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
128
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 175 publications
(139 citation statements)
references
References 46 publications
(78 reference statements)
4
128
0
1
Order By: Relevance
“…Instead of focusing on pre-defined functional groups, future studies could benefit from taking a trait-based approach, using measurable characteristics of the different components of communities (across trophic levels) rather than categorical groups, as has recently become the focus in biodiversity-ecosystem functioning research (De Deyn et al, 2008;Hillebrand and Matthiessen, 2009;Reiss et al, 2009). In contrast to our expectation, under the assumption of overall increased plant photosynthetic activity with fertilisation given higher productivity (De Deyn et al, 2011), we did not find effects of fertiliser application on the C uptake and transfer to microbes. However, our results are in line with the study of Hill et al (2007) where mineral N application also did not affect C assimilation rates in Lolium perenne, as opposed to the strong effect of elevated CO 2 levels.…”
Section: Species and Management Effects On C Fluxmentioning
confidence: 66%
See 2 more Smart Citations
“…Instead of focusing on pre-defined functional groups, future studies could benefit from taking a trait-based approach, using measurable characteristics of the different components of communities (across trophic levels) rather than categorical groups, as has recently become the focus in biodiversity-ecosystem functioning research (De Deyn et al, 2008;Hillebrand and Matthiessen, 2009;Reiss et al, 2009). In contrast to our expectation, under the assumption of overall increased plant photosynthetic activity with fertilisation given higher productivity (De Deyn et al, 2011), we did not find effects of fertiliser application on the C uptake and transfer to microbes. However, our results are in line with the study of Hill et al (2007) where mineral N application also did not affect C assimilation rates in Lolium perenne, as opposed to the strong effect of elevated CO 2 levels.…”
Section: Species and Management Effects On C Fluxmentioning
confidence: 66%
“…In a long-term grassland restoration experiment Smith et al (2003Smith et al ( , 2008 showed that cessation of mineral fertiliser use and the seeding of target plant species increased plant species richness and the abundance of soil fungi, compared to soil bacteria. These restoration treatments also enhanced the rate of soil C and N accumulation (De Deyn et al, 2011), suggesting potential management impacts on short-term C fluxes through plants and soil biota.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Although we cannot rule out that the proposed mechanisms are particularly pronounced at the field site of The Jena Experiment, the underlying relationships between plant diversity and soil carbon storage 17,24 , soil microbial biomass and activity 37,45,46 , and root biomass 24,47 have been reported in several independent experimental settings providing some evidence that the proposed links are of general significance. This leads us to reconsider the role of soil microorganisms as sources rather than sinks for slow-cycling organic matter.…”
mentioning
confidence: 99%
“…The observed increase in carbon storage with plant diversity 17 therefore either reflects higher primary production 18,19 or longer persistence of plant-derived organic materials due to slower decomposition 10,16 . Increased plant residue inputs also provide more substrate for soil microorganisms, resulting in a more active and more abundant microbial community 20 .…”
mentioning
confidence: 99%